ETIKA KECERDASAN BUATAN ARTIFICIAL INTELLIGENCE (AI) DALAM PENGAMBILAN KEPUTUSAN KEBIJAKAN PUBLIK - Jihan Rofifatuz Zahabiyyah; Alya Nabila Septiana; Hayat (Wacana: Jurnal Ilmu Sosial dan Ilmu Politik Interdisiplin, 2024)
The primary objective of this study is to examine the ethical implications of incorporating Artificial Intelligence (AI) into public policy decision-making processes. The research underscores the critical importance of ethical considerations in the development and implemntation of AI technologies to addres potential risks whitin social contexts. Employing a qualitative analysis approach, the study draws on a comprehensive review of literature and data from various sources to explore the ethical dimension od AI in decision-making. The findings hinglight the necessity of integrating ethical frameworks into AI systems to ensure their responsible and effective use in public policy. The results also demonstrate how AI can enhance decision-making processes while simultaneously addressing ethical challenges. The study concludes by emphasizing the importance of establishing robust ethical guidelines to govern AI applications in public policy, ensuring that these technologies are developed and utilized in ways that are socially responsible and beneficial for society.